Bacteroides fragilis Toxin Induces Cleavage and Proteasome Degradation of E-cadherin in Human Breast Cancer Cell Lines BT-474 and MCF7 - Da-Hye KANG; Sang-Hyeon YOO; Ju-Eun HONG; Ki-Jong RHEE (Korean Journal of Clinical Laboratory Science, 2023)
Enterotoxigenic Bacteroides fragilis (ETBF) has been reported to promote colitis and colon cancer through the secretion of B. fragilis toxin (BFT), a zinc-dependent metalloprotease. In colonic epithelial cells, BFT induces the cleavage of E-cadherin into the 80 kDa ectodomain and the 33 kDa membrane-bound intracellular domain. The resulting membrane-tethered fragment is then cleaved by γ-secretase forming the 28 kDa E-cadherin intracellular fragment. The 28 kDa cytoplasmic fragment is then degraded by an unknown mechanism. In this study, we found that the 28 kDa E-cadherin intracellular fragment was degraded by the proteasome complex. In addition, we found that this sequential E-cadherin cleavage mechanism is found not only in colonic epithelial cells but also in the human breast cancer cell line, BT-474. Finally, we report that staurosporine also induces E-cadherin cleavage in the human breast cancer cell line, MCF7, through γ-secretase. However, further degradation of the 28 kDa E-cadherin intracellular domain is not dependent on the proteasome complex. These results suggest that the BFT-induced E-cadherin cleavage mechanism is conserved in both colonic and breast cancer cells. This observation indicates that ETBF may also play a role in the carcinogenesis of tissues other than the colon.